Geochemical characteristics of the braided river reservoir in block 19 of the sulige gas field - Hu, Zhangming; Hu, Mingyi; Xiong, Xianyue; Zheng, Lijun; Wu, Nan; Guang, Youhui; Hu, Xiaoling; Huang, Xin (Frontiers in Energy Research, 2023)
The sand body structure and geochemical characteristics of braided river reservoirs are the key geological factors affecting gas production and development effects. The Sulige gas field in the Ordos Basin is an important large-scale gas-producing layer. Owing to the control of sedimentary facies, the geological structure of the sand body changes greatly and its connectivity is poor. The geological characteristics have not yet been elucidated, and this is an important problem restricting the development of the Sulige Gas Field. To solve this problem, this study focuses on the braided river reservoir of the Shihezi Formation in Block 19 of the Sulige Gas Field, conducts geological surveys in the study area, analyzes the geological and geochemical characteristics of the reservoir, and obtains samples through drilling. Through a thin-section test, gas-water two-phase experiment, and simulation test, the braided river reservoir configuration and pore and gas-water characteristics are obtained. The results show that the reservoir lithology in the study area is mainly composed of quartz sandstone, lithic sandstone, and quartzy lithic sandstone, with a porosity of 3%–13% and a permeability of (0.05–0.7) × 10−3 m2. The reservoir has low porosity and low permeability. After drilling samples were obtained, 32 thin-section rock samples were selected. The pore types of the block reservoir mainly (82.9%) consisted of intragranular and intergranular dissolved pores. The difference in pore structure was mainly reflected by the size and distribution of the throat. The distribution of physical properties was 6%–10%, the gas saturation was 61%, the NMR effective porosity was 7.49%, the permeability was 4.08 × 102 μm2, and the physical properties were relatively good. In terms of the study area, the average thickness of the single braided channel in the lower section of He 8 was 4.7 m, the average width of the channel was 963 m, and the composite channel was distributed in a potato shape, parallel to the direction of the main flow. The average length of the channel was 2,147 m and the average width was 844 m. As the porosity increased, the efficiency of gas-driven water also increased, and there was a linear positive correlation between porosity and gas-driven water efficiency. With the increase in movable water saturation, the water-air ratio became larger and water production was greater. In low-amplitude structures and under low-permeability background conditions, for reservoirs with good local pore structure and physical properties, the water remaining at the bottom of the reservoir or sand body was controlled by the accumulation conditions or the weak structural differentiation after accumulation. In terms of the gas and water produced simultaneously in the study area, gas production was less than 2 × 104 m3/d and water production was relatively large at more than 10 m3/d; gas and water were mainly distributed in the downdip part of the main channel structure or in the island lens-shaped permeable sand bodies trapped by the surrounding tight layers. The study results provide theoretical data support for the exploration and production of the Sulige Gas Field.